Longitudinal trends in the prevalence of hyperuricaemia and chronic kidney disease in hypertensive and normotensive adults - Krajčoviechová, Alena; Wohlfahrt, Peter; Bruthans, Jan; Šulc, Pavel; Lánská, Věra; Borghi, Claudio; Cífková, Renata (Blood pressure, 2020)
The purpose: To evaluate longitudinal trends in the prevalence of hyperuricaemia and chronic kidney disease (CKD) in Czech adults with and without arterial hypertension (HT).Materials and methods: Two independent cross-sectional surveys were performed in 2006-2009 and 2015-2018, each screening involving 1% population random sample of the general population of nine districts of the Czech Republic aged 25-64 years, stratified by age and gender. Hyperuricaemia was defined as serum uric acid ≥ 420 μmol/l in men, and ≥ 360 μmol/l in women. CKD was defined as estimated glomerular filtration rate < 60 ml/min/1.73 m2 and/or albumin/creatinine ratio ≥ 3 mg/mmol.Results: Final analyses included 3504 individuals examined in 2006-2009, and 2309 in 2015-2018. The overall prevalence of hyperuricaemia increased from 16.4% to 25.2% in men (p < 0.001), and from 7.6% to 10.9% in women (p < 0.001), whereas the overall prevalence of CKD declined from 6.8% to 3.6% in men (p = 0.001), and from 7.6% to 4.8% in women (p < 0.001). There was no interaction between HT and hyperuricaemia in either gender; the increase in hyperuricaemia prevalence was observed both in hypertensive and normotensive adults and was accompanied by the increased prevalence of abdominal obesity. Contrarily, there was an interaction between HT and CKD in both men (p < 0.001) and women (p = 0.011); the CKD prevalence declined only in hypertensive individuals, specifically in those using antihypertensive medication and was accompanied by the increased use of renin-angiotensin-aldosterone system (RAS) inhibitors and calcium channel blockers (CCBs).Conclusions: Over the period of 10 years, the overall prevalence of hyperuricaemia increased, while the prevalence of CKD decreased. An increase in the prevalence of hyperuricaemia was observed both in hypertensive and normotensive individuals and was accompanied by an increase in the prevalence of abdominal obesity. A decline in the prevalence of CKD was only observed in hypertensive individuals and was accompanied by the increased use of RAS inhibitors and CCBs.
Keywords: Cross-Sectional Studies; Male; Hyperuricemia; hypertenze; Middle Aged; longitudinální studie; chronická renální insuficience; prevalence; Adult; dospělí; mužské pohlaví; Hypertension; lidé; krevní tlak; ženské pohlaví; Humans; Renal Insufficiency, Chronic; Blood Pressure; průřezové studie; Prevalence; Longitudinal Studies; Female; lidé středního věku; hyperurikemie